Penerapan Kepatuhan Syariah Pada Jual-Beli Dropshipping Fashion Di Marketplace Frozenshop.Com - Muhamad Reyhan Aldabena (Syntax Idea, 2022)
Sharia compliance broadly is the application of Islamic principles, sharia and its traditions in financial and banking transactions as well as other related businesses, sharia compliance applies in Indonesia in accordance with the Fatwa of the National Sharia Council (DSN) because the DSN fatwa is the embodiment of sharia principles and rules that must be adhered to. adhered to, including in business matters such as dropshipping. Dropshipping is a buying and selling system involving 3 parties, namely buyers, sellers and suppliers (providers of goods). The seller in this context is referred to as a dropshipper. Frozenshop.com is one of the men's fashion suppliers in Indonesia that they open opportunities for dropshippers to sell their goods back to consumers. The purpose of this study is to find out how the implementation of sharia compliance in the sale and purchase of dropshipping fashion in the Frozenshop.com Marketplace and how the legal implications of the dropshipping fashion sale and purchase scheme in the Frozenshop.com Marketplace online which still contain elements of gharar. The results of this study are the application of sharia compliance in the sale and purchase of dropshipping fashion in the Frozenshop.com marketplace is not in accordance with sharia compliance, where the goods are not owned directly by the dropshipper when the dropshipper sells the goods. Meanwhile, the Legal Implication for the dropshipping fashion sale and purchase scheme in the online Frozenshop.com marketplace which still contains an element of gharar, is a dropshipping sale and purchase scheme with goods that have not obtained permission from Frozenshop.com which acts as a supplier. So the legal implications of buying and selling goods sold by the dropshipper are canceled or Faskah.